Patient Satisfaction with Anesthesia Technician Services Cesarean Section Patients Under Eracs - Heriyani Heriyani; Dwi Novitasari; Wilis Sukmaningtyas; Awal Tunis Yantoro; Agus Dwi Yulianto (Indonesian Journal of Global Health Research, 2026)
Patient satisfaction is a complex concept that relies heavily on the patient's personal judgment. When expectations are not met, patients tend to seek alternative care that is perceived as easier and faster. The study aims to describe the characteristics and level of satisfaction with Anesthesia Technician services among SC patients with ERACS at Muhammadiyah Palembang Hospital. This study employed a cross-sectional design with a convenience sampling technique involving 48 patients undergoing Enhanced Recovery After Cesarean Surgery (ERACS). Data were collected using questionnaires that had been validated through expert judgment and tested for reliability using Cronbach’s alpha (α > 0.7). Data were analyzed descriptively to present respondent characteristics and bivariately using the Chi-square test to examine relationships between variables. The results of the study showed the characteristics of SC patients with ERACS at Muhammadiyah Palembang Hospital, based on age showed that the majority of patients were 26-35 years old with 27 respondents (56.2%), education showed that the majority of patients' education was high school with 22 respondents (45.8%), and characteristics based on work showed that the majority of patients' work was housewives 39 respondents (81.2%). Patient satisfaction levels showed that the majority of patients who underwent SC with ERACS had a high level of satisfaction, with 27 respondents (56.2%). This study shows that the majority of respondents are in the category of high satisfaction level, attributed to the quality of anesthesiologist services meeting patient expectations.